Pengaruh Coupons, Discount, dan Marketing Event terhadap Impulse Buying pada Platform Pengiriman Online Grabfood di Yogyakarta - Rossy Anjelika Devinda Suwito; Hari Nuurweni (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2021)
This study aims to determine the effect of coupons, discounts and marketing events on impulse buying on the Grabfood online delivery platform in Yogyakarta. The sampling technique uses the Non-Probability Sampling model with the purposive sampling method, which is to determine the sample with the consideration that consumers have made transactions at least 1 (one) time a week on the Grabfood application in Yogyakarta. The number of samples in this study were 120 respondents. The tests used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, F test, multiple linear regression test, t test, coefficient of determination test. The results of this study indicate that the variables of coupons, discounts and marketing events have a positive and significant effect on impulsive purchases on the Grabfood online delivery platform in Yogyakarta.